Ternary Sn‐Ti‐O Electrocatalyst Boosts the Stability and Energy Efficiency of CO2 Reduction. Issue 31 (3rd June 2020) - Wen, Guobin; Ren, Bohua; Park, Moon G.; Yang, Jie; Dou, Haozhen; Zhang, Zhen; Deng, Ya‐Ping; Bai, Zhengyu; Yang, Lin; Gostick, Jeff; Botton, Gianluigi A.; Hu, Yongfeng; et al.
Abstract: Simultaneously improving energy efficiency (EE) and material stability in electrochemical CO2 conversion remains an unsolved challenge. Among a series of ternary Sn‐Ti‐O electrocatalysts, 3D ordered mesoporous (3DOM) Sn0.3 Ti0.7 O2 achieves a trade‐off between active‐site exposure and structural stability, demonstrating up to 71.5 % half‐cell EE over 200 hours, and a 94.5 % Faradaic efficiency for CO at an overpotential as low as 430 mV. DFT and X‐ray absorption fine structure analyses reveal an electron density reconfiguration in the Sn‐Ti‐O system. A downshift of the orbital band center of Sn and a charge depletion of Ti collectively facilitate the dissociative adsorption of the desired intermediate COOH* for CO formation. It is also beneficial in maintaining a local alkaline environment to suppress H2 and formate formation, and in stabilizing oxygen atoms to prolong durability. These findings provide a new strategy in materials design for efficient CO2 conversion and beyond. Abstract : Trade off : With a trade off between active‐site exposure and structural stability, a 3D ordered mesoporous (3DOM) structured Sn‐Ti‐O material achieves cathodic energy conversion efficiency (EEca ) as high as 71.5 % over 200 hours for electrochemical conversion of CO2 into CO. It benefits from an electron density reconfiguration at the Sn‐Ti‐O interface and a local alkaline environment to improve CO selectivity and stabilize lattice oxygen atoms.